THE EFFECT OF RELATIONSHIP MARKETING ON SERVICE QUALITY AND CUSTOMER SATISFACTION IN THE HOSPITALITY SECTOR IN GHANA: THE MODERATING ROLE OF SERVICE PROVIDERS’ EMOTIONAL INTELLIGENCE - Frimpong Opuni, Frank; Opoku, Emmanuel; Oseku-Afful, Mary (British Journal of Marketing Studies, 2014)
This study assesses the effect of relationship marketing on service quality and customer satisfaction from the perspective of the moderating role of emotional intelligence in the hospitality sector in Ghana. A descriptive quantitative research technique is employed. A random sample of 384 each of customers and customer service attendants of hotels, leisure centres, resorts and five-star restaurants in Accra are used as the source of data. According to findings, emotional intelligence makes a strong positive effect on relationship marketing at 5% significance level, r (288) = .785, p = .000. Though relationship marketing makes a strong positive effect on service quality (r = .712, p < .05) and customer satisfaction (r = .318, p < .05), these effects degenerate into negative ones when the effect of emotional intelligence on relationship marketing is controlled for. It is therefore recommended that firms in the hospitality sector give priority to equipping their customer service attendants with emotional intelligence to maximise service quality and customer satisfaction